Intensive Care Management of Children Intubated for Croup: A Retrospective Analysis. Issue 2 (March 2016) - Gelbart, B.; Parsons, S.; Sarpal, A.; Ninova, P.; Butt, W.
Croup remains the commonest reason for acute upper airway obstruction in children, yet there are scarce contemporary data of airway management in those requiring intubation. We performed a retrospective analysis of the intensive care management of children intubated for croup in two quaternary paediatric intensive care units: Royal Children's Hospital Melbourne, Australia, and Alberta Children's Hospital, Calgary, Canada. Patients intubated for less than three days were compared with those intubated for greater than three days. Patients less than 10 kg body weight were compared to those greater than 10 kg. Demographic, clinical and microbiological data were recorded. Seventy-seven cases of croup requiring intubation were identified. The median duration of intubation was 60 hours. Parainfluenza was the most common viral aetiology, detected in 30% of cases. Antibiotics were prescribed in 51% of patients. Corticosteroids were prescribed pre-intubation in two-thirds of patients and all post-intubation, with the median dose being prednisolone 3 mg/kg/day. Primary extubation failure occurred in 6.5% of patients. Neither the duration of intubation nor patient size were associated with extubation failure. An air leak test was performed in 69% of patients and poorly predicted extubation success. One non-urgent tracheostomy was performed and there was one death from hypoxic ischaemic encephalopathy. Endotracheal tube leak is poorly recorded and may not predict successful extubation.